Analysis of Review of Literature on Employee Retention Strategies of Higher Education Institutions in Bengaluru - Reddy, Dr. Kiran; Koundal, Mr. Gourav (The journal of contemporary issues in business and government, 2023)
The success of the most competitive companies throughout the world, including higher education institutions, lies in their highly skilled employees on which these institutions spend millions to retain them. Literature reveals the cost of losing best employees to be enormous - beyond monetary quantification. Also worth noting is that the loss of one competent employee to a competitor adds up to the competitor's advantage. The study analyzes literature review on employee retention strategies of higher education institutions. This paper aims to provide a selective literature review of articles published in the last decade on employee retention strategies. The review also found that this research lacked a theoretical underpinning and that more research studies are needed to empirically validate some of the key variables emerging in this area of research. The study concludes with a literature synthesis and recommendations for future research.